Assessment of low-molecular-weight antioxidants in Francisella tularensis infected hosts: comparison of two rodents with different susceptibility to tularemia - Pohanka, Miroslav; Bandouchova, Hana; Novotny, Ladislav; Pavlis, Oto; Treml, Frantisek; Sedlackova, Jana; Pikula, Jiri (Neuro endocrinology letters, 2009)
OBJECTIVES: Bacterium Francisella tularensis is the causative agent of tularemia disease. It is a zoonosis accompanied with high mortality when untreated. Small rodents and hares, in particular, are natural reservoirs of tularemia. Despite physiological similarity of common hosts, tularemia exerts different mortality rates. The pathogenesis of tularemia is still not fully understood. The main pathway is associated with proliferation in macrophages after activation by reactive oxygen species in phagosomes. DESIGN: A fully virulent strain of F. tularensis subsb. holarctica was used for infection of laboratory BALB/c mice (Mus musculus) and common voles (Microtus arvalis) representing murine and microtine species. The total level of low-molecular- weight antioxidants (LMWA) in plasma was assayed by cyclic voltammetry. RESULTS: It was found that common voles are more resistant to tularemia progression when compared to mice. When LMWA assayed, surprising changes in LMWA levels were found. Both mice and common voles were infected with high dose resulting in overall mortality. While there was a quick depletion of LMWA in plasma in mice, common voles were even able to increase LMWA. CONCLUSION: It seems that LMWA play an important role in the organism s protection during tularemia. The ability to compensate the LMWA losses and increase levels of antioxidants in common voles is probably responsible for its lower susceptibility to tularemia.
Keywords: molekulová hmotnost; náchylnost k nemoci; Disease Susceptibility; Mice; Tularemia; antioxidancia; Animals; myši inbrední BALB C; Arvicolinae; zvířata; Antioxidants; myši; Mice, Inbred BALB C; tularemie; Molecular Weight